1996
DOI: 10.1159/000154797
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of an Anion Exchanger in Cortisol Release from Bovine Adrenocortical Cells

Abstract: In this study the influence of probenecid as inhibitor of the renal excretory system for organic anions was tested on the release of cortisol from primary cultures of bovine adrenocortical cells. ACTH-stimulated cortisol release (30 min to 24 h) was inhibited by probenecid (Ki = 0.093 mM). Analysis of steroid synthesis with 3H-pregnenolone as precursor indicated that part of the inhibition resulted from an attenuation of steroid synthesis by probenecid. The increased intracellular cortisol levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Indeed, earlier experiments on bovine adrenal cells in primary culture provided evidence for the involvement of transporters for organic anions in the release of cortisol. The inhibitor of OATs, probenecid decreased cortisol release, and extracellular PAH and glutarate increased it by trans-stimulation (17,18). Bovine adrenal cells exhibited probenecid-sensitive PAH uptake that was inhibited by cortisol (18), indicating a transporter common for PAH, glutarate, and cortisol.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, earlier experiments on bovine adrenal cells in primary culture provided evidence for the involvement of transporters for organic anions in the release of cortisol. The inhibitor of OATs, probenecid decreased cortisol release, and extracellular PAH and glutarate increased it by trans-stimulation (17,18). Bovine adrenal cells exhibited probenecid-sensitive PAH uptake that was inhibited by cortisol (18), indicating a transporter common for PAH, glutarate, and cortisol.…”
Section: Discussionmentioning
confidence: 95%
“…Using the stop-flow peritubular capillary microperfusion method, Ullrich et al (19) described cortisol transport across the basolateral membrane of the proximal tubule cell of the rat kidney. Recent studies showed an inhibition of cortisol release from primary cultures of bovine adrenocortical cells by probenecid and trans-stimulation of cortisol release by p-aminohippurate (PAH) and glutarate in the incubation medium (17). Further investigations on bovine adrenocortical cells demonstrated an uptake of radioactively labeled PAH, which was inhibited by probenecid and unlabeled PAH.…”
mentioning
confidence: 99%
“…In our former study [7], we have shown that 1 mM PAH in the incubation medium trans-stimulated cortisol release out of the cells approximately 1.6-fold. If cortisol and PAH share a common transporter, unlabeled PAH or cortisol at the outside, i.e., in the incubation medium, should cis-inhibit 3 H-PAH uptake.…”
Section: Resultsmentioning
confidence: 81%
“…Recently we demonstrated that adrenocorticotropic hormone (ACTH) stimulated cortisol release from bovine adrenocortical cells was inhibited by probenecid and trans-stimulated by PAH [7]. In that paper, we also described the expression of probenecid-inhibitable PAH transport after injection of mRNA from adrenocortical cells in Xenopus oocytes which suggested the existence of mRNA encoding a PAH transporter in the adrenocortical cells.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation